Defeating malaria: new weapons against one of our deadliest foes. Issue 7 (4th September 2020) - Greener, Mark
Abstract : Malaria remains a global threat, with resistance to antimalarials an increasing risk and no vaccine available despite decades of research. However, recent studies on the benefits of combining antimalarials, emerging treatments with novel mechanisms of action, and several new vaccines in clinical trials indicate there is reason to be hopeful.